A study on determination of sports tourism preferences in Malaysia - Mohd Noor, Nur Syaqira Husnina; Saad, Mazni (2019)
Tourism industry is known as one of the largest contributors of national and global revenues through sports events and tourism. The purpose of this research is to identify the most preferable type of sports tourism among Malaysian and to examine the factors of social, economic and environmental that influence sports visitors to travel in Malaysia. However, at least some articles are exploring the specific type of sports activities that are loved and participated by Malaysian. In response to this statement, this study wants to emphasize the preferable type of sports tourism among Malaysians based on their social, economic and environmental factors. This study used simple random sampling and an online survey form distributed among Malaysian. Based on SPSS analysis, 53 respondents responded to the survey showed the result that only environmental factors give significant impact toward preferences in sport tourism while social and economic factors are partially supported in this study.